Photographic section: An Introdiction - Fotta, Martin; Sabino-Salazar, Mariana (Romano džaniben, 2021)
A brief text introducing the work of photographers from Latin America who document the life of local Roma: Rogerio Ferrari, Lorenzo Armendariz, Ruth Margarita Campos Cabello, Toño García Romero, and Luciana Sampaio.
Keywords: photographs; arts; image of Roma; Latin America